Global solution for wave equation involving the fractional Laplacian with logarithmic nonlinearity - Bidi Younes; Abderrahmane Beniani; Khaled Zennir; Zayd Hajjej; Hongwei Zhang (Electronic Research Archive)
We construct the global existence for a wave equation involving the fractional Laplacian with a logarithmic nonlinear source by using the Galerkin approximations. The corresponding results for equations with classical Laplacian are considered as particular cases of our assertions.